An Analysis of The Students’ Difficulties in Translating Indonesian Text Into English - Safhira Qur’aini Haqmawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the translation difficulties encountered by seventh-semester English Education students at Nurul Jadid University when translating Indonesian texts into English. Using a qualitative descriptive design, data were collected from 15 female students through written translation tests, semi-structured interviews, and classroom observations. An adapted error analysis framework based on Baker’s (1992) categories—lexical, grammatical, semantic/contextual, idiomatic/cultural, and stylistic/structural—was applied to identify and classify errors. Findings reveal that lexical errors (31.6%) and grammatical errors (27.7%) were the most dominant, reflecting students’ limited vocabulary and difficulty applying grammar rules in authentic contexts. Other challenges included semantic misunderstandings, literal translation of idioms, and stylistic weaknesses affecting fluency and cohesion. Contributing factors included insufficient English proficiency, lack of translation strategy awareness, overreliance on machine translation tools, limited exposure to authentic English input, and curricular limitations in translation training. The study recommends incorporating strategy-based instruction, expanding exposure to authentic materials, and revising the curriculum to balance English-to-Indonesian and Indonesian-to-English translation practice.